NATURE IDIOMS IN ENGLISH AND KAZAKH LANGUAGES: NATURE IDIOMS IN ENGLISH AND KAZAKH LANGUAGES - Nurjanova, Bagila (Журнал иностранных языков и лингвистики, 2025)
Idioms are a necessarily portion of any language, reflecting the culture, values, and worldview of its speakers. They are expressions that pass on implications not straightforwardly related to the person words inside them. In this article, we'll examine nature expressions in both English and Kazakh, looking at their suggestions, utilization, and cultural importance. By comparing figures of speech from these two languages, we pick up knowledge into how diverse cultures perceive and relate to the common world.